A Review of Contemporary Retail Formats in Emerging India - Basu, Rituparna (Indian Journal of Marketing, 2013)
Trends of globalization coupled with reduced trade barriers are inducing competitive retailers to shift focus away from the hitherto attractive developed markets towards investing in the emerging underserved geographic markets. However, getting it right in the emerging markets requires thoughtful judgments on the existing structure and dynamics of the new markets. In the wake of relaxing regulatory climate, India's position as an attractive retail destination calls for scrutiny and introspection. While retail practitioners are critically exploring alternatives to come up with innovative India-specific retail business models or formats, an account of the modern retail landscape in India comes handy. Hence, the present paper attempts to present an account of the current retail formats in emerging India as a collation of evidences and estimations available from literature and other sources of academic interest that could be used as a point of reference by indigenous retail theoreticians and practitioners.